Successful Repair of Esophageal Atresia with Tracheoesophageal Fistula and Interrupted Inferior Vena Cava: A Rare Case Report - Mu, Xiao Long; Wang, Junqiu (European Journal of Pediatric Surgery Reports, 2024)
Esophageal atresia (EA) with tracheoesophageal fistula (TEF) is a congenital anomaly that can present complex surgical challenges, especially when accompanied by rare vascular conditions like an interrupted inferior vena cava (IVC). The division of the azygos vein is a common part of TEF repair, but in the presence of an interrupted IVC, this can lead to life-threatening complications. We report the case of a newborn diagnosed with EA, TEF, and interrupted IVC, successfully treated through thoracotomy. This case underscores the importance of prenatal and postnatal imaging to diagnose vascular anomalies prior to TEF repair, ensuring the preservation of the azygos vein to prevent fatal outcomes. Raising awareness of this rare association is crucial to optimizing surgical planning and outcomes.
Keywords: esophageal atresia; tracheoesophageal fistula; interrupted inferior vena cava